Management and Funding Challenges Facing Higher Institutions in Some African Countries - Nwogbo, David C. (West African Journal of Open and Flexible Learning, 2017)
The paper examined the problem of managing higher education in Africa where leadership problem and ideological issues have combined to limit tertiary education funding. As funding is limited and lacks sustainability, enrolment is fast increasing due to population growth rates. The methodology of the paper is based on qualitative research design and relied on secondary data to carry out its analysis of higher education funding in Africa. The paper adopted a co relational and critical approach of data analysis. The paper concludes that unless a sustainable policy on higher education funding in Africa is instituted, African countries will continue to battle with the problem of funding. The recommended a paradigm shift in higher education leadership that places emphasis on innovation and strategic visioning for increased higher education funding.Résumé : L’article examinait le problème de la gestion de l'enseignement supérieur en Afrique où les problèmes de la direction et les problèmes idéologiques se sont combinés pour limiter le financement de l'enseignement supérieur. Comme le financement est limité et n'est pas viable, les inscriptions augmentent rapidement en raison des taux de croissance démographique. La méthodologie du document est basée sur la conception de recherches qualitatives et s'appuie sur des données secondaires pour effectuer son analyse du financement de l'enseignement supérieur en Afrique. Le document a adopté une approche co-relationnelle et critique de l'analyse des données. Le document conclut qu'à moins qu'une politique durable de financement de l'enseignement supérieur en Afrique ne soit instituée, les pays africains continueront à lutter contre le problème du financement. Il a recommandé un changement de paradigme dans la gestion de l'enseignement supérieur qui met l'accent sur l'innovation et la vision stratégique pour un financement accru de l'enseignement supérieur.
Keywords: higher education; funding; enrolment; leadership; ideology